Introducing E-Commerce And Internet Development In Education Institutions - Azahar, Noor Hamiza (2008)
This project particularly introduces a new e-learning system (ELS) and internet development to Multimedi auniversity as well as other educational institutions. The proposed system is user friendly, simple and interactive, and does not contain too many complicated functions.